Measurement of mixed materials and analysis of plutonium isotope ratio based on fast neutron multiplicity - Kaile Li; Sufen Li; Xingfu Cai; Yonggang Huo; Fei Wang (AIP Advances)
Fast neutron multiplicity measurement technology has achieved good measurement results for single fission nuclide materials, such as uranium and plutonium. However, when measuring mixed materials, the deviation is large, and it is necessary to obtain the proportion of each isotope in advance by other analysis methods. Therefore, in this paper, the liquid scintillation detection model is built by Geant4, and the variation characteristics of Rossi-α distribution and coincidence gate factors fd and ft are analyzed. It is found that Rossi-α distribution is sensitive to the spatial layout of the detection system, and the disturbance of fd and ft will cause large deviation to the measurement results, and the effect is opposite. The fast neutron multiplicity measurement of the mixed materials was studied, and the measurement results were corrected by the isotope abundance ratio and the rated spontaneous fission yield of each isotope. On this basis, a calculation method of isotope mass ratio based on fast neutron multiplicity measurement is also proposed. The mass ratio of each isotope can be inversely solved by fast neutron multiplicity equation and modified multiplication coefficient. The method is proved to be accurate and effective, and the deviation is within 10%. It reduces the difficulty of solving mixed materials, expands the method of isotope abundance measurement, and promotes the development of verification technology.